Nonfinancial performance evaluation as significant area of strategic business management - Hornungová, Jana (Business: Theory and Practice, 2017)
The main aim of this paper is to provide the answer to the questions: Which areas of the company play an important role in the evaluation of the performance? Which areas are considered to be important? Due to the fact that the business environment is constantly changing, changes also occur in the trends relating to performance. Traditional financial performance measures have been highly criticized and the need identified to integrate non-financial perspectives, such as the level of innovation, degree of motivation, intellectual capital, and other criteria. Intellectual capital is often a crucial factor in the creation of value in a company. Based on the research, employees and customers are one of the most important areas in the companies from the selected area. At the same time, dependence among these company’s areas and company’s profit has been identified. Furthermore, it has been found whether the introduction of social responsibility into business strategy affects responsible behaviour just in the working environment (as this is geared specifically to employment area). Thus, as regards business strategy and support to work environment, in this case no relationship has been indicated, therefore it is not possible to say that if companies apply social responsibility strategy, they support mainly the working environment.